Stomatheraphy: influences and repercussions on the professional career (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To analyze the influences and repercussions of enterostomal therapy on the career of nurses. Methods: Descriptive, exploratory study with quantitative approach, conducted in 2014. The sample consisted of 29 nurses graduated from the Nursing School of the University of São Paulo and the University of Taubaté. The data were collected through a questionnaire and analyzed by SPHINXR software. The results were discussed in the light of the literature on the subject. Results: The continuity of the studies provided the nurse a career with promotions, management positions or even a career redirection. The work environment influenced the achievement of the specialty (21/79%). The participants worked in several types of institutions and their positions were diverse, thus presenting options for those who want to pursue a career in the area. Conclusion: The job market, as well as the environment in which the nurse is inserted, most of the time plays a defining role when the subject is the choice of a specialization.